2010
DOI: 10.1002/stem.405
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept Underlying Stem Cell Lineage Skewing That Explains the Detrimental Effects of Thiazolidinediones on Bone

Abstract: Bone-marrow adipogenesis is an aging-related phenomenon and is correlated with osteoporosis. The latter is a prevalent bone disease in the elderly leading to increased fracture risk and mortality. It is widely hypothesized that the underlying molecular mechanism includes a shift in the commitment of mesenchymal stem cells (MSCs) from the osteogenic lineage to the adipogenic lineage. Lineage skewing is at least partially a result of transcriptional changes. The nuclear transcription factor peroxisome proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 62 publications
4
66
0
Order By: Relevance
“…PPAR-γ has been shown in preclinical studies to promote the differentiation of mesenchymal stem cells into adipocytes rather than osteoblasts [46], and to promote osteoclast differentiation and increase osteoclast numbers [45]. In addition, exposure to TZDs appears to induce osteoblast and osteocyte apoptosis [47][48][49]. A reduction in the number of osteocytes and osteoblasts has the potential for prolonged negative effects on bone, given the relatively long differentiation periods and lifespans of these cell types [50].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ has been shown in preclinical studies to promote the differentiation of mesenchymal stem cells into adipocytes rather than osteoblasts [46], and to promote osteoclast differentiation and increase osteoclast numbers [45]. In addition, exposure to TZDs appears to induce osteoblast and osteocyte apoptosis [47][48][49]. A reduction in the number of osteocytes and osteoblasts has the potential for prolonged negative effects on bone, given the relatively long differentiation periods and lifespans of these cell types [50].…”
Section: Discussionmentioning
confidence: 99%
“…128,129 It has also been proposed that rosiglitazone is able to accelerate both fat and bone cell maturation through the PPARg2 isoform in adipocytes and PPARg1 in osteoblasts, with a substantial build-up of ROS. 130 Yet, others have reported that induction of adipogenesis through PPARg stimulation does, in fact, necessarily reduce osteoblast differentiation and function, supporting the notion of a shared pool of progenitor cells. 123,[131][132][133] A number of prospective and retrospective observational investigations have aimed to determine whether TZD use is associated with a negative effect on bone density in humans.…”
Section: Diabetic Medicationsmentioning
confidence: 97%
“…The use of thiazolidinediones (glitazones) may lead to bone loss (49) and more fractures (50), because stem cells preferentially differentiate into adipocytes rather than osteoblasts (51,52,53).…”
Section: Impact Of Antidiabetic Medicationsmentioning
confidence: 99%